Analisis Putusan Mahkamah Konstitusi Terkait Dengan Penetapan Tersangka Sebagai Objek Praperadilan (Studi Putusan Nomor 73/Pid.Pra/2018/Pn.Mdn) - Panggabean, Josep (Iuris Studia: Jurnal Kajian Hukum, 2020)
A person's freedom can be limited for the sake of law enforcement, as stated in article 50 of the Criminal Code which states that: